2013
DOI: 10.1093/nar/gkt818
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA identification over mouse brain development by integrative modeling of chromatin and genomic features

Abstract: In silico prediction of genomic long non-coding RNAs (lncRNAs) is prerequisite to the construction and elucidation of non-coding regulatory network. Chromatin modifications marked by chromatin regulators are important epigenetic features, which can be captured by prevailing high-throughput approaches such as ChIP sequencing. We demonstrate that the accuracy of lncRNA predictions can be greatly improved when incorporating high-throughput chromatin modifications over mouse embryonic stem differentiation toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 84 publications
1
45
0
2
Order By: Relevance
“…The results together with others (Lv et al, 2013a;Lv et al, 2013b;Ng et al, 2012b;Qureshi and Mehler, 2012) have highlighted the importance of lncRNAs in regulation of cellular fate in neural cells and brain. Increasing evidences suggested that lncRNAs can control epigenetic targeting via their ability to bind RNA, DNA and protein (Guttman and Rinn, 2012;Mercer and Mattick, 2013;Tsai et al, 2010).…”
Section: High-throughput Approaches To Study the Lncrnas In Cns Develsupporting
confidence: 65%
See 1 more Smart Citation
“…The results together with others (Lv et al, 2013a;Lv et al, 2013b;Ng et al, 2012b;Qureshi and Mehler, 2012) have highlighted the importance of lncRNAs in regulation of cellular fate in neural cells and brain. Increasing evidences suggested that lncRNAs can control epigenetic targeting via their ability to bind RNA, DNA and protein (Guttman and Rinn, 2012;Mercer and Mattick, 2013;Tsai et al, 2010).…”
Section: High-throughput Approaches To Study the Lncrnas In Cns Develsupporting
confidence: 65%
“…Actually, many transcriptomic studies have revealed the dynamic lncRNA expression profiles and their functions among developing, fetal and adult tissues, in additional to embryonic stem (ES) cells Sheik Mohamed et al, 2010), neural cell subtypes Aprea et al, 2013;Lin et al, 2011), and brain Ponjavic et al, 2009;Lv et al, 2013a;Lv et al, 2013b).…”
Section: Lncrnas In the Central Nervous Systemmentioning
confidence: 99%
“…Indeed, a nuclear isoform of PTEN antisense transcript and its cytosolic counterparts have opposite effects on PTEN expression, due to differential sequestration of small ncRNAs within the two cellular compartments (Poliseno et al 2010;Jalali et al 2012). Owing to these diverse molecular mechanisms, lncRNAs are now known as important regulators of fundamental processes such as development, imprinting, and cell differentiation (Kretz 2013;Lee and Bartolomei 2013;Lv et al 2013). They are also involved in stress responses to heat, hypoxia, or DNA damage (Jolly et al 2004;Bertozzi et al 2011;Wu et al 2012;Place and Noonan 2013;Wan et al 2013;Yang et al 2013a;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that both protein-coding genes and non-coding genes were associated with diverse chromatin signals Lv et al, 2013). H3K4me3 and H3K27me3 are known to mark promoters for activating and repressing gene expression respectively (Li et al, 2012), while H3K36me3 generally marks the elongation sites of transcribed regions (Lv et al, 2013).…”
Section: Characterization Of Transcriptional Activity and Conservatiomentioning
confidence: 99%
“…H3K4me3 and H3K27me3 are known to mark promoters for activating and repressing gene expression respectively (Li et al, 2012), while H3K36me3 generally marks the elongation sites of transcribed regions (Lv et al, 2013). So we examined these related transcriptional element of all non-coding RNAs.…”
Section: Characterization Of Transcriptional Activity and Conservatiomentioning
confidence: 99%